Distinguishing the Regional Atmospheric Controls on Precipitation Isotopic Variability in the Central-Southeast Portion of Brazil - Santos, Vinícius dos [UNESP] (2022)
Precipitation isotope ratios (O and H) record the history of water phase transitions and fractionation processes during moisture transport and rainfall formation. Here, we evaluated the isotopic composition of precipitation over the central-southeastern region of Brazil at different timescales. Monthly isotopic compositions were associated with classical effects (rainfall amount, seasonality, and continentality), demonstrating the importance of vapor recirculation processes and different regional atmospheric systems (South American Convergence Zone-SACZ and Cold Fronts-CF). While moisture recycling and regional atmospheric processes may also be observed on a daily timescale, classical effects such as the amount effect were not strongly correlated (δ18O-precipitation rate r ≼ −0.37). Daily variability revealed specific climatic features, such as δ18O depleted values (∼6‰ to −8‰) during the wet season were associated with strong convective activity and large moisture availability. Daily isotopic analysis revealed the role of different moisture sources and transport effects. Isotope ratios combined with d-excess explain how atmospheric recirculation processes interact with convective activity during rainfall formation processes. Our findings provide a new understanding of rainfall sampling timescales and highlight the importance of water isotopes to decipher key hydrometeorological processes in a complex spatial and temporal context in central-southeastern Brazil.